2008
DOI: 10.1111/j.1365-2052.2008.01774.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete porcine MSTN gene and expression levels in pig breeds differing in muscularity

Abstract: Myostatin (MSTN), a transforming growth factor beta superfamily member, is an essential factor for the growth and development of muscle mass. The protein functions as a negative regulator of muscle growth and is related to the so-called double-muscling phenotype in cattle, where a series of mutations renders the gene inactive. One particular breed of pigs, the Belgian Piétrain, also shows a heavily muscled phenotype. The similarity of muscular phenotypes between the double-muscled cattle and Piétrain pigs indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
111
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(120 citation statements)
references
References 28 publications
8
111
0
1
Order By: Relevance
“…The gene sequence has been shown to be highly conserved across vertebrate species (McPherron and Lee, 1997). Loss-of-function mutations associated with increased skeletal-muscle mass and other pleiotropic effects have been detected in several species, including cattle (Grobet et al, 1997), mice (Szabò et al, 1998), humans (Schuelke et al, 2004), sheep (Clop et al, 2006), dogs (Mosher et al, 2007), chickens (Ye et al, 2007;McFarland et al, 2007;Yang et al, 2003) and putatively pigs (Stinckens et al, 2008). These evidences support the hypothesis that also MSTN function could be highly conserved among vertebrates.…”
Section: Introductionsupporting
confidence: 66%
“…The gene sequence has been shown to be highly conserved across vertebrate species (McPherron and Lee, 1997). Loss-of-function mutations associated with increased skeletal-muscle mass and other pleiotropic effects have been detected in several species, including cattle (Grobet et al, 1997), mice (Szabò et al, 1998), humans (Schuelke et al, 2004), sheep (Clop et al, 2006), dogs (Mosher et al, 2007), chickens (Ye et al, 2007;McFarland et al, 2007;Yang et al, 2003) and putatively pigs (Stinckens et al, 2008). These evidences support the hypothesis that also MSTN function could be highly conserved among vertebrates.…”
Section: Introductionsupporting
confidence: 66%
“…In two Norwegian sheep breeds, two different mutations in the MSTN coding region are associated with carcass conformation and fatness ). In pigs, mutations identified in noncoding regulatory regions affect the level of MSTN gene expression and/or are associated with growth, muscle mass and other carcass traits (Stinckens et al, 2008). Esmailizadeh et al (2008) found a SNP in the MSTN gene affecting birth, growth, carcass and beef quality traits of Bos taurus.…”
Section: Discussionmentioning
confidence: 99%
“…A different mutation creating a regulatory miRNA site was found in the sheep myostatin gene generating an miRNA binding site in the myostatin mRNA, leading to down-regulation of the expression of the myostatin gene in the high-meatiness Texel sheep breed (Clop et al, 2006). However, no evidence exists for a mutation in the porcine myostatin gene (Stinckens et al, 2008). Therefore, we focused on the mechanism of muscle development and growth during prenatal pig development.…”
Section: Prenatal Muscle Tissue Development Related To Post-mortem Mementioning
confidence: 99%